PENGARUH PROSES REKRUTMEN TERHADAP KINERJA KARYAWAN PADA CV.GADJAH MADA SARANA PALEMBANG - Yunita Ningsih; Amelia Lestari; Yuli Anita (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2020)
This study examines the effect of the recruitment process on employee performance on the CV. Gadjah Mada Sarana Palembang .. The purpose of this study is to find out the recruitment process influencing the performance of employees at CV. Gadja Mada Sarana Palembang and To find out which recruitment process is most influential on employee performance at CV. Gadja Mada Sarana Palembang. The Recruitment Process Against Employee Performance in the CV. Gadjah Mada Facilities contain norms and values ​​of belief that direct the behavior of members of the organization. Therefore, organizations should provide a vehicle for employees to internalize the culture so that they are able to apply it at work. This research is carried out on the CV. Gadjah Mada Sarana Palembang. From 42 people taken as samples by sending them questionnaires as many as 42 questionnaires. The results obtained from the regression analysis using SPSS version 15 indicate that there is an influence of the Recruitment Process on employee performance on CV. Gadja Mada Sarana Palembang